2020
DOI: 10.1108/jes-11-2018-0413
|View full text |Cite
|
Sign up to set email alerts
|

Does the African Growth and Opportunity Act (AGOA) impact EU-15 imports from Africa?

Abstract: PurposeAt the heart of the African Growth and Opportunity Act (AGOA) are substantial trade preferences, which coupled with the Generalised System of Preferences (GSP) grant a wide range of goods produced in qualified African countries duty-free access to the USA. To be AGOA-eligible, countries are assessed annually on their progress in undertaking appropriate economic, institutional and human rights reforms. This paper seeks to cover new grounds by exploring whether exports of apparel to US crowds out EU-15's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The finding is similar to that of Naumann (2016) , who argued that SSA-AGOA countries, Nigeria exceeds other countries in terms of average export. In a related way, Mahabir et al. (2020) , engaged the Gravity Model and found that a strong positive impact of the bilateral trade between the US and Africa.…”
Section: Methodology Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The finding is similar to that of Naumann (2016) , who argued that SSA-AGOA countries, Nigeria exceeds other countries in terms of average export. In a related way, Mahabir et al. (2020) , engaged the Gravity Model and found that a strong positive impact of the bilateral trade between the US and Africa.…”
Section: Methodology Results and Discussionmentioning
confidence: 99%
“…The finding is similar to that of Naumann (2016), who argued that SSA-AGOA countries, Nigeria exceeds other countries in terms of average export. In a related way, Mahabir et al (2020), engaged the Gravity Model and found that a strong positive impact of the bilateral trade between the US and Africa. The study found that, for every proportion rise in exports to the USA, there is a less than proportionate increase in exports to the EU, indicating a higher utilisation of the special waiver.…”
Section: Federal Ministry Of Industry Trade and Investmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The study underscores the adverse impact of stringent rules of origin and successive trade liberalization in advanced countries that is leading to the erosion of preferential benefits. Mahabir et al (2020) examining whether exports of apparel under AGOA crowds out EU-15's imports from SSA show the complementarity of African exports to the two markets and that every percentage growth in exports to the USA is associated with a less than proportionate increase in exports to the EU-15, indicating a higher utilization of the special waiver. A survey-based study by Karingi et al (2012) also found that a majority of private sector respondents believed that AGOA was critical for their exports and economic relations while a quarter of the respondents stated that AGOA was not important.…”
Section: Literature Reviewmentioning
confidence: 99%